PEMANFAATAN NEURAL NETWORK DENGAN METODE BACKPROPAGATION UNTUK MEMFILTER SPAM - Testiana, Gusmelia (Al 'Ilmi : Jurnal Pendidikan MIPA, 2012)
Email Spam is email that is sent to thousands of email users in a sustainable manner Typiclly, it contains unwanted promotional priduct, service, business, pornographi, viruses and emails. This study uses Neural Network whith a back propagation methods as email classification. The email will be extracted based on header that consists of content type, sender domains, the perfix which is based an the stages of extraction ward, removing every stopword  word, removing affixes and TFIDF calculation. The emails which are used in this study were taken from Spam Assassin. Based on this research, neural network which mostly used back propagation method are able to classify emails based on its cargoy.